Stricture Prevention after Extensive Endoscopic Submucosal Dissection of Neoplastic Barrett's Esophagus: Individualized Oral Steroid Prophylaxis. (14th April 2019) - Probst, Andreas; Ebigbo, Alanna; Märkl, Bruno; Schaller, Tina; Anthuber, Matthias; Messmann, Helmut
Abstract : Introduction . Endoscopic resection (ER) exceeding ≥75% of the esophageal circumference is accompanied with a high stricture risk regardless of the resection method. The ideal strategy for stricture prevention is not well defined today. Different approaches have been reported but data are limited to the resection of squamous cell neoplasia. The aim of this study was to assess the efficacy of an individualized oral steroid regimen to prevent strictures after extensive ER in neoplastic Barrett's esophagus (NBE). Materials and Methods . Over a 50-month period, endoscopic submucosal dissection (ESD) was performed in 193 patients with NBE. 23 patients with resections exceeding 75% of the circumference were included. 19 resection ulcers were noncircumferential (NCR) while 4 were circumferential (CR). Stricture prevention was performed using oral prednisolone starting with a daily dose of 50 mg and standard tapering over 8 weeks (50/40/30/25/20/15/10/5 mg). Tapering was individualized according to the ulcer healing process (assessed endoscopically in the first tapering period and before stopping the steroids). Data were analyzed retrospectively. Results . Stricture rates were 5.3% (1/19) for NCR and 100% (4/4) for CR (p < 0.001 ). The only stricture in the NCR group was seen in a patient who had stopped steroids without any reason after few days. 12/19 patients received standard tapering over 8 weeks (63.1%). According to the individual ulcer healing, treatment was prolonged to 9-10 weeks in 4/19 (21.1%) and shortened to 7 weeks in another 2/19 (10.5%). After CR, all patients needed endoscopic balloon dilatation (median 6.5 sessions; range 3-14 sessions for 8-40 weeks). Side effects of the steroid therapy were not noted. Conclusion . Oral prednisolone therapy with an endoscopy-based individualized tapering regimen is effective in avoiding strictures after NCR of Barrett's neoplasia. After CR, the stricture risk is not sufficiently decreased. CR should be restricted to circumferential neoplasia which is a very rare scenario in neoplastic BE.